(untitled) (Chittagong University Journal of Biological Sciences, 2025)
This study investigated the effects of cadmium (Cd), lead (Pb), zinc (Zn), and copper (Cu) on some biochemical constituents like chlorophyll, nitrogen and protein levels in rice. A pot experiment was conducted using agricultural loamy soil amended with graded concentrations of Cd, Pb, Zn, and Cu salts, with untreated soil serving as control. Rice leaf samples were collected after 45 days of transplantation in in-situ conditions and analyzed for chlorophyll content. Nitrogen and protein content in rice grains were determined after harvest at ripening. Results revealed significant (p<0.05) reductions in chlorophyll a, chlorophyll b, and total chlorophyll across all treatments, with Cd exerting the most severe inhibitory effect, followed by Pb, Cu, and Zn. Similarly, nitrogen and protein contents declined under metal exposure, with Cd and Pb causing the greatest reductions, while Zn and Cu showed comparatively moderate toxicity. These findings demonstrate that heavy metal stress disrupts pigment biosynthesis, nitrogen metabolism, and protein synthesis in rice, thereby compromising its physiological performance and nutritional quality. Chittagong Univ. J. B. Sci. Vol. 13 (1&2): 86-92, 2025